Managing, organising and sharing fine-grained data in the spatial design disciplines – an evaluation of a GeoNode prototype - Rautenbach, Victoria-Justine (University of Pretoria, 2021)
Dissertation (MSc (Geoinformatics))--University of Pretoria, 2021.